Feasibility and safety of a self-developed sleeve for the endoscopic removal of refractory foreign body incarceration - Yu, Guangqiu; Li, Li; Zhang, Yirui; Zhong, Xiaohuan; Wang, Jing; Jiang, Ling; Hu, Duanmin; Zhou, Weixia (Frontiers in Surgery, 2023)
Objective This study aimed to assess the feasibility and safety of a novel self-designed sleeve for the endoscopic removal of a refractory incarcerated foreign body in the upper gastrointestinal tract (UGIT). Methods An interventional study was conducted between June and December 2022. A total of 60 patients who underwent an endoscopic removal of a refractory incarcerated foreign body from the UGIT were randomly allocated to the self-developed sleeve and the conventional transparent cap. The study evaluated and compared the operation time, successful removal rate, new injury length at the entrance of the esophagus, new injury length at the impaction site, visual field clarity, and postoperative complications between the two groups. Results The success rates of the two cohorts in the foreign body removal display no significant discrepancy (100% vs. 93%, P = 0.529). Nevertheless, the methodology of the novel overtube-assisted endoscopic foreign body removal has culminated in a significant reduction in the removal duration [40 (10, 50) min vs. 80 (10, 90) min, P = 0.01], reduction in esophageal entrance traumas [0 (0, 0) mm vs. 4.0 (0, 6) mm, P < 0.001], mitigation of injuries at the location of the foreign body incarceration [0 (0, 2) mm vs. 6.0 (3, 8) mm, P < 0.001], an enhanced visual field (P < 0.001), and a decrement in postoperative mucosal bleeding (23% vs. 67%, P < 0.001). The self-developed sleeve effectively negated the advantages of incarceration exclusion during removal. Conclusion The study findings support the feasibility and safety of the self-developed sleeve for the endoscopic removal of a refractory incarcerated foreign body in the UGIT, with advantages over the conventional transparent cap.